Mechanochromic Luminescence Characteristics of Pyridine‐Terminated Chromophores in the Solid State and in a Poly(vinyl alcohol) Matrix. Issue 11 (5th September 2014) - Kondo, Mizuho; Miura, Seiya; Okumoto, Kentaro; Hashimoto, Mayuko; Kawatsuki, Nobuhiro
Abstract Mechanoresponsive luminophores containing different substituted pyridine rings at the molecular terminus are synthesized and their photoluminescence properties are investigated. The solid chromophore with a 4‐substituted pyridine ring exhibits a reversible photoluminescent color change, while the 2‐substituted chromophore shows only a small change in luminescence, and the 3‐substituted chromophore displays an irreversible photoluminescent color change with mechanical grinding. A change of the sample color in response to mechanical grinding is also achieved for a dye‐dispersed poly(vinyl alcohol) film. Furthermore, a simultaneous acid and mechanoresponsive photoemission color change is achieved in the dye‐dispersed film.